The National Drug Abuse Treatment Clinical Trials Network: forging a partnership between research knowledge and community practice - Liu D; Sparenborg S; Tai B; Straus M (Dove Medical Press, 2011)
Betty Tai, Steven Sparenborg, David Liu, Michele StrausCenter for the Clinical Trials Network, National Institute on Drug Abuse, National Institutes of Health, United States Department of Health and Human Services, Bethesda, MD, USAAbstract: The National Drug Abuse Treatment Clinical Trials Network (CTN) has faced many challenges over its first eleven years. This review explores some of these challenges and the paths the CTN took to meet these challenges, including: designing clinical trials that reflect the CTN’s mission and changing public health needs, finding the synergies in the varied expertise of clinical treatment providers and academic researchers, promoting evidence-based practices and expanding the Network into mainstream medical practices to reach a broader patient population. Included in this exploration are specific examples from CTN clinical trials.Keywords: Clinical Trials Network, drug abuse, addiction